Effects of MGA and prostaglandin on estrus induction and synchronization in cows and heifers - Perry, R.C.; Boyd, G.W.; Goehring, T.B.; Corah, L.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Four trials were conducted to evaluate the effectiveness of Melegestrol Acetate (MGA ®) and prostaglandin (PGF) in inducing and synchronizing estrus. In trial 1, treated heifers were fed MGA for 7 days and given a PGF injection on either the first or last day of MGA feeding. The 7-day estrus response was higher (P<.01) for treated heifers than untreated controls. In trial 2, treated cows were fed MGA for 7 days and given a PGF Injection on the last day of MGA feeding or 13 days after the last day of MGA feeding. The 7-day estrus response was also higher (P<.01) in treated cows. In trial 3, 59 cows were fed MGA for 7 days followed by a PGF injection, and exposed to bulls for 66 days. The MGA-PGF treatment was ineffective in synchronizing estrus and hastening conception. In trial 4, feeding MGA for 7 days successfully synchronized estrus in. cycling cows, but first service conception rates were reduced by 10% in the Kansas study and by 16% in a four state study.
Keywords: Beef; MGA; Prostaglandin; Estrus; Synchronization